Pupils’ Misconceptions about Atoms Juxtaposed to the Structure of Matter as Imagined by Ancient Thinkers - Hejnová, Eva; Hejna, Dalibor (Scientia in educatione, 2018)
In this review study, we present the most common misconceptions about atoms that have been identified in foreign research. The frequency of these misconceptions is exemplified by a study we carried out in the Czech Republic, involving a set of 170 pupils consisting of one class of fourth graders at an eight-year grammar school and six classes of ninth graders from various basic schools, all of whom were quizzed on their understanding of atoms. At the same time, we show how some of their misconceptions parallel those of ancient thinkers, focusing in particular on Greek atomists. By shedding light on their thought processes, we also want to show how the knowledge of the formation of historical pre-scientific theories is important for understanding how contemporary science works and what paradigm it is based on.